2014
DOI: 10.1124/jpet.113.211243
|View full text |Cite
|
Sign up to set email alerts
|

Novel TRPM8 Antagonist Attenuates Cold Hypersensitivity after Peripheral Nerve Injury in Rats

Abstract: Abnormal cold sensitivity is a common feature of a range of neuropathies. In the murine somatosensory system, multiple aspects of cold sensitivity are dependent on TRPM8, both short term and in response to peripheral nerve injury. The specialized nature of cold-sensitive afferents and the restricted expression of TRPM8 render it an attractive target for the treatment of cold hypersensitivity. This current study examines the effect of a novel TRPM8 antagonist (M8-An) in naive and spinal nerveligated rats throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…Many studies have demonstrated that TRPM8 and TRPA1 receptor mediate cold detection 12,14,16,17,30 , however, in line with our results some contradictory studies using TRPA1 antagonists and TRPA1 KO mice failed to show a reduction of cold sensitivity in physiological conditions 13,15 . Moreover, the lack of TRPM8 contribution in DP cold detection, evidenced by our observation that cold-induced c-Fos upregulation was not prevented in TRPM8 KO mice, would be explained by the small proportion (5%) of neurons innervating the DP that express TRPM8.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Many studies have demonstrated that TRPM8 and TRPA1 receptor mediate cold detection 12,14,16,17,30 , however, in line with our results some contradictory studies using TRPA1 antagonists and TRPA1 KO mice failed to show a reduction of cold sensitivity in physiological conditions 13,15 . Moreover, the lack of TRPM8 contribution in DP cold detection, evidenced by our observation that cold-induced c-Fos upregulation was not prevented in TRPM8 KO mice, would be explained by the small proportion (5%) of neurons innervating the DP that express TRPM8.…”
Section: Discussionsupporting
confidence: 85%
“…TRPM8 is activated at non-noxious cold temperatures (<25 °C) and clearly contribute to cool temperature perception 10 whereas TRPA1 is a polymodal receptor activated by noxious cold stimulation (<17 °C), chemical irritants, and appears to be involved in mechanosensation as well 11,12 . Previous studies showed that the pharmacological blockade and genetic deletion of TRPM8 or TRPA1 reduce cold sensitivity in physiological, inflammatory and neuropathic conditions 1217 .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that antagonism of the TRPM8 receptor inhibits behavioural and spinal neuronal responses to innocuous and noxious cooling in SNL but not naive rats [53]. Surprisingly, the TRPM8 agonist reported here displayed identical effects.…”
Section: Discussionmentioning
confidence: 46%
“…Additionally, TRPM8-immunoreactive staining has been observed in the urothelium and in nerve fibers distributed throughout the suburothelium, and a marked increase in the number of fine-caliber nerve fibers immunoreactive for TRPM8 was found in patients with BPS compared with controls (P < 0.05) (Mukerji et al, 2006). Furthermore, TRPM8 antagonists lower body temperature in rats, and might be used to treat cold hypersensitivity and hyperalgesia in several neuropathic conditions, including complex regional pain syndrome and trigeminal neuralgia, peripheral nerve injury, and chemotherapy-induced neuropathy (Almeida et al, 2012;Gavva et al, 2012;Patel et al, 2014;Winchester et al, 2014). Moreover, TRPM8 has higher expression in prostate cancer tissue than in normal prostate tissue, and has also been detected in tumors of the breast, colon, lung, skin, and pancreas (Tsavaler et al, 2001;Yee et al, 2010;Okamoto et al, 2012).…”
Section: Discussionmentioning
confidence: 99%